THE MANY FACES OF RENUNCIATION: A COMPARATIVE STUDY OF ASCETICISM ACROSS WORLD RELIGIONS - Gulgulia, Aarti; Pandey, Shruti Kant; Jain, Veersagar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Asceticism refers to a deliberate lifestyle choice marked by restraint from indulgence in material and sensory pleasures, pursued through self-discipline and simplified living. This approach to life plays a pivotal role in numerous religious traditions worldwide. The present study delves into the complex dimensions of renunciation by examining its conceptual origins, theological interpretations, and lived practices. It spans a diverse array of traditions, including Indian religions such as Hinduism, Buddhism, and Jainism; Abrahamic faiths like Christianity, Islam, and Judaism; as well as selected indigenous belief systems. The aim is to illuminate how different cultures have envisioned and practiced ascetic ideals across time and geography. While the motivations and manifestations of asceticism vary from salvation and liberation to mystical union and ethical purification the renunciatory impulse universally represents a conscious distancing from worldly attachments in favor of higher spiritual or moral ideals. By engaging in comparative analysis, this paper highlights both the convergences and divergences in global ascetic traditions, examining how religious ideologies negotiate the tension between world-renunciation and spiritual engagement.